THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT ON CUSTOMER LOYALTY THROUGH POSTPAID CUSTOMER SATISFACTION PT. TELKOMSEL INDONESIA - Muhammad Rais; Mursalim Nohong; Abdul Razak Munir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2022)
This study aims to determine the effect of Customer Relationship Management (CRM) on customer loyalty through postpaid customer satisfaction of PT Telkomsel Indonesia. The method used in this research is the descriptive method and the quantitative method. The descriptive method is used to find out how consumers respond to the service quality of PT Telkomsel in applying the CRM method to customer loyalty through customer satisfaction. While quantitative methods are used to examine certain populations or samples, collect data, and use research instruments. The research data were processed and analyzed using the path analysis method (path analysis). The results of the path I analysis test show a coefficient correlation (R2) of 0.990 and the results of the second path analysis test show a coefficient correlation (R2) of 0.993 which indicates that the relationship between the independent and dependent variables is very strong because it has a positive R-value and is close to one. The indirect effect of the CRM variable on customer loyalty through customer satisfaction using the Sobel test. The results of this test show the value of the t count > t table, which is 2.870 > 2.776. So it can be concluded that there is a significant influence of CRM on Customer Loyalty through Customer Satisfaction.